The ripple effect of surface water on dryland ecosystems - Amanda L. Subalusky; Christopher L. Dutton; Robert A. McCleery (Trends in Ecology & Evolution, 2026)

Bioreactors on the Move: How Animals Contribute to Microbial Community Coalescence and Shape Ecosystem Function - Christopher L. Dutton; Audrey Goeckner; Tavis Goldwire; Carsten G. B. Grupstra; Dawson Houghtaling; Lee (Emily) Nonnamaker; Amanda Subalusky (Environmental Microbiology, 2026)
Microbiome community coalescence—the mixing of separate microbial communities and their environments resulting in a novel community—represents an important but understudied ecological process at the animal‐environment interface. Here, we propose that animals function as “mobile bioreactors” across landscapes, ingesting environmental microbes that undergo selective filtering within the animal gut that are then deposited back into the environment alongside the animal's native microbiota. This coalescence of animal and environmental microbiomes can significantly alter ecosystem processes including nutrient cycling, organic matter decomposition, and trophic interactions. We synthesize emerging evidence from terrestrial, freshwater, and marine ecosystems demonstrating how animal‐facilitated microbial coalescence influences ecosystem functioning. Through case studies of hippos in African rivers, fish on coral reefs, and earthworms in soil, we illustrate how these coalescence events create novel microbial communities with distinct functional capabilities. We identify methodological approaches for investigating these phenomena and outline key knowledge gaps, particularly regarding the persistence of animal microbiota in environmental settings and their quantitative contribution to ecosystem processes. Here we highlight the importance of studying animal‐environmental coalescence events with far reaching implications for our understanding of ecosystem processes, animal health, and environmental resilience.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Integrating the Bright and Dark Sides of Aquatic Resource Subsidies—A Synthesis - Cornelia W. Twining; Andreu Blanco; Christopher Dutton; Martin J. Kainz; Eric Harvey; Carmen Kowarik; Johanna M. Kraus; Dominik Martin‐Creuzburg; Tarn Preet Parmar; N. Roxanna Razavi; Nicole Richoux; Gregoire Saboret; et al. (Ecology Letters, 2025)
Aquatic and terrestrial ecosystems are linked through the reciprocal exchange of materials and organisms. Aquatic‐to‐terrestrial subsidies are relatively small in most terrestrial ecosystems, but they can provide high contents of limiting resources that increase consumer fitness and ecosystem production. However, they also may carry significant contaminant loads, particularly in anthropogenically impacted watersheds. Global change processes, including land use change, climate change and biodiversity declines, are altering the quantity and quality of aquatic subsidies, potentially shifting the balance of costs and benefits of aquatic subsidies for terrestrial consumers. Many global change processes interact and impact both the bright and dark sides of aquatic subsidies simultaneously, highlighting the need for future integrative research that bridges ecosystem as well as disciplinary boundaries. We identify key research priorities, including increased quantification of the spatiotemporal variability in aquatic subsidies across a range of ecosystems, greater understanding of the landscape‐scale extent of aquatic subsidy impacts and deeper exploration of the relative costs and benefits of aquatic subsidies for consumers.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fecal steroids as a potential tool for conservation paleobiology in East Africa - Andrew C. Kemp; Christopher H. Vane; Alexander W. Kim; Christopher L. Dutton; Amanda L. Subalusky; Stuart K. Kemp; Andrew C. Parnell (Biodiversity and Conservation, 2022)

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Novel “filter pellet” sample preparation strategy for quantitative LA-ICP-MS analysis of filter-bound sediments: a “green chemistry” alternative to sediment fingerprinting in Tanzania’s Ruvu River basin - Sarah C. Jantzi; Christopher L. Dutton; Amartya Saha; Rosemary Masikini; Jose R. Almirall (Journal of Soils and Sediments, 2019)

Organic matter and nutrient inputs from large wildlife influence ecosystem function in the Mara River, Africa - Amanda L. Subalusky; Christopher L. Dutton; Laban Njoroge; Emma J. Rosi; David M. Post (Ecology, 2018)
Animals can be important vectors for the movement of resources across ecosystem boundaries. Animals add resources to ecosystems primarily through egestion, excretion, and carcasses, and the stoichiometry and bioavailability of these inputs likely interact with characteristics of the recipient ecosystem to determine their effects on ecosystem function. We studied the influence of hippopotamus excretion/egestion and wildebeest carcasses, and their interactions with discharge, in the Mara River, Kenya. We measured nutrient dissolution and decomposition rates of wildlife inputs, the influence of inputs on nutrient concentrations and nutrient limitation in the river and the influence of inputs on biofilm growth and function in both experimental streams and along a gradient of inputs in the river. We found that hippopotamus excretion/egestion increases ammonium and coarse particulate organic matter in the river, and wildebeest carcasses increase ammonium, soluble reactive phosphorus, and total phosphorus. Concentrations of dissolved carbon and nutrients in the water column increased along a gradient of wildlife inputs and during low discharge, although concentrations of particulate carbon decreased during low discharge due to deposition on the river bottom. Autotrophs were nitrogen limited and heterotrophs were carbon limited and nitrogen and phosphorus colimited upstream of animal inputs but there was no nutrient limitation downstream of inputs. In experimental streams, hippo and wildebeest inputs together increased biofilm gross primary production ( GPP) and respiration ( R ). These results differed in the river, where low concentrations of hippo inputs increased gross primary production ( GPP ) and respiration ( R ) of biofilms, but high concentrations of hippo inputs in conjunction with wildebeest inputs decreased GPP . Our research shows that inputs from large wildlife alleviate nutrient limitation and stimulate ecosystem metabolism in the Mara River and that the extent to which these inputs subsidize the ecosystem is mediated by the quantity and quality of inputs and discharge of the river ecosystem. Thus, animal inputs provide an important ecological subsidy to this river, and animal inputs were likely important in many other rivers prior to the widespread extirpation of large wildlife.